Satellite RNA 보유 Cucumber mosaic virus(CMV)의 고추 CMV병에 대한 교차방어 효과 - 최장경(Jang Kyung Choi); 성미영(Mi Young Sung); 정혜진(Hye Jin Jung); 홍진성(Jin Sung Hong); 이상용(Sang Yong Lee) (Sigmulbyeong yeon'gu, 2001)
Two attenuated Cucumber mosaic virus (CMV) isolates, Paf-CMV and Rs2-CMV that had been selected from CMV isolates associated with satellite RNA (satRNA) were tested for cross-protection effect in pepper plants. The viruses selected as attenuated strains appeared to be identical serologically and physically to the challenge virus (Mf-CMV), but they were lower in the dilution end-point of infectivity of crude sap than Mf-CMV When symptoms were observed in several indicator plants after inoculation, Paf-CMV and Rs2-CMV were symptomless or showed mild mosaic symptoms while another satRNA isolate Ap-CMV developed severe mosaic symptoms on the leaves as Mf-CMV. The nucleotide sequences of the satRNAs were determined by sequencing full-length cDNA clones. Paf-, Rs2- and Ap-satRNAs were 386, 335, and 347 nucleotides long, respectively, The sequences were then compared with the other known Y-satRNA, revealing that nucleotide sequences of the satRNAs consisted of 5'- and 3'-terminal conserved regions. However variations occurred on the middle regions of the sequences, especially those related to symptom interference, showing significant differences between Paf-satRNA and other isolates. Infectious transcripts of Paf-satRNA and Rs2-satRNA induced mild mosaic symptoms in pepper plants when supported by genomic RNAs of Mf-CMV. Under greenhouse conditions, Paf-CMV and Rs2-CMV were tested for cross-protection effect in pepper and tobacco (Nicotiana tabacum cv, Xanthi nc) plants against Mf-CMV. No symptoms were developed on the plants vaccinated with Paf-CMV until 3 weeks after inoculation with the virulent strain; however another attenuated isolate, Rs2-CMV, showed less effectiveness in cross-protection. Depending on the concentration of the challenged virus, symptoms sometimes appeared later in the upper leaves. However, in plants challenged with low concentrations (below 0.2 mg/ml) of the challenge inoculum, symptoms caused by the virulent strain did not develop on the plants vaccinated with Paf-CMV. In the field experiments, the number of pepper plants with severe mosaic symptoms in the control plots was progressively increased after transplanting and reached approximately 50% after 50 days. On the other hand, the incidence of mosaic disease appeared very low on the plants that had received the protective inoculation with Paf-CMV. 기주반응 실험을 통하여 무병징 또는 엷은 병징을 발현하는 satRNA 보유 Paf-CMV 및 Rs2-CMV를 고추 CMV병의 방제를 위한 약독바이러스로 공시하여 교차방어효과를 검정하였다. 공시한 satRNA-CMV는 모두 agar gel diffusion test에서 강독계로 공시한 Mf-CMV의 항원과 융합하는 침강선을 나타내 subgroup I의 혈청 형으로 판단되었다. 이들 약독계 satRNA-CMV의 물리적성질은 내희석성이 $10^{-4}$으로, 강독계 Mf-CMV나 satRNA를 보유하고 있는 Ap-CMV보다 낮게 나타났으나, 내열성 및 내보존성 은 차이를 보이지 않았다. 공시한 satRNA의 염기서열을 결정한 결과, Rs2-satRNA는 335염기, Ap-satRNA 347염기, Paf-satNA 386염기로 구성되어 있었다. 이들 염기서열을 이미 보고된 Y-CMV의 satRNA와 비교한 결과, 양 말단 영역 특히 5'말단으로부터 80염기 및 3'말단으로부터 174염기는 안정된 conserved sequence를 나타냈다. 그러나 중간영역의 염기서열에서는 .많은 변이를 나타냈고, 특히 병징과 관련된 domain으로 보고된 영역에서 Paf-satRNA의 염기서열은 다른 계통의 satRNA에 비하여 많은 차이를 보였다. 각 satRNA의 cDNA로부터 전사시킨 transcript RNA를 Mf-CMV의 게놈RNA와 혼합하여 고추에 접종한 결과, 본래의 각 satRNA-CMV를 접종하였을 때와 마찬가지로 Paf-satRNA 및 Rs2-satRNA의 transcript 와 혼합한 Mf-CMV에 감염된 고추의 병징이 약하게 발현되었다. 선발된 약독CMV의 강독계 바이러스에 대한 교차방어효과를 검정하기 위하여 Paf-CMV 및 Rs2-CMV를 접종한 고추와 담배에 강독 Mf-CMV를 challenge한 후 교차방어 지속효과를 검정한 결과, Paf-CMV를 접종한 고추와 담배는 모두 Mf-CMV를 challenge 접종한 3주후까지 병징이 발현되지 않았으나, Rs2-CMV를 접종한 식물은 challenge 2주 후에 약 반수의 개체에서 강독계 병징이 발현되었다. 또한 challenge바이러스의 농도별 교차방어효과에서도 Paf-CMV를 접종한 고추에 정제한 Mf-CMV를 0.2 mg/ml 이하의 농도로 challenge한 경우, 접종 30일이 되었을 때까지 병징이 발현되지 않았으나, Rs2-CMV에서는 일부의 개체에서 병징이 발현되어 강독계에 대한 교차방어의 효과가 일정하게 나타나지 않았다. 한편 고추의 유묘에 약독CMV를 접종한 다음, 포장에 재배하면서 바이러스병징이 발현되는 개체를 조사한 결과, 약독 CMV접종 30-60일 후에 Paf-CMV 접종구에서 1.8-6.4%, Rs2-CMV 접종구에서 8.2-18.3%그리고 무접종구에서 2.7-47.2%의 바이러스병징이 발현됨으로서 Paf-CMV의 강독계 CMV의 감염에 대한 교차방어효과가 안정되고 높게 나타났다..